Desarrollo de un prototipo orientado a la seguridad del hogar, vinculado a un dispositivo de geo localización para niños con trastorno por déficit de atención con hiperactividad (TDAH) y trastorno de conducta (TC) - Alban Basante, Jenny Estefania (2021)
Being a father or mother is not easy, but being the father of a child with ADHD complicates the task even more, since once the parents have accepted and understood their child's disorder, it is time to take measures with which they can grow up healthy. and happy, this requires constant family work and in many cases it will be necessary to introduce changes and adaptations in the family dynamics [2]. ADHD is a medical disorder in which the development and activity of the brain of these people present some differences that affect attention, the ability to sit still and self-control.